2011
DOI: 10.1021/ic200161m
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic Oxotungsten(V) Complexes Containing the Hydrotris(3,5-dimethylpyrazol-1-yl)borate Ligand

Abstract: Sky-blue Tp*WOCl(2) has been synthesized from the high-yielding reaction of Tp*WO(2)Cl with boron trichloride in refluxing toluene. Dark-red Tp*WOI(2) was prepared via thermal decarbonylation followed by aerial oxidation of Tp*WI(CO)(3) in acetonitrile. From these precursors, an extensive series of mononuclear tungstenyl complexes, Tp*WOXY [X = Cl(-), Y = OPh(-), SPh(-); X = Y = OPh(-), 2-(n-propyl)phenolate (PP(-)), SPh(-), SePh(-); XY = toluene-3,4-dithiolate (tdt(2-)), quinoxaline-2,3-dithiolate (qdt(2-)), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 97 publications
2
29
0
Order By: Relevance
“…3,11 Comparative model studies are very important to understand the nature of W and Mo enzymes. 2,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Comprehensive studies have been reported in a review. 2 In the case of square-pyramidal monooxo bis(dithiolate) complexes, the bond length of the multiple WuO bond is longer than that of the MouO bond, although the bond dissociation energy of WuO is larger than that of MouO.…”
Section: Introductionmentioning
confidence: 99%
“…3,11 Comparative model studies are very important to understand the nature of W and Mo enzymes. 2,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Comprehensive studies have been reported in a review. 2 In the case of square-pyramidal monooxo bis(dithiolate) complexes, the bond length of the multiple WuO bond is longer than that of the MouO bond, although the bond dissociation energy of WuO is larger than that of MouO.…”
Section: Introductionmentioning
confidence: 99%
“…However, further evidence is provided by mass spectrometry, which clearly shows the molecular peak at 659 m / z . The related dihalide species [Tp′W(O)( X ) 2 ] ( X = Cl, I) were already synthesized, characterized, and examined by spectroelectrochemistry showing specific absorption in the UV/Vis region 12. As reported by Young , the dichlorido complex is sky‐blue, whereas the diiodido complex is dark red.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of possible solvents (CH 2 Cl 2 , DMF, and THF) were mentioned for the EPR measurements of [Tp*WO(XPh) 2 ] (X = O, S), without further specifying the one actually used. 41 EPR Parameter Calculations. The four-component relativistic mDKS method with restricted kinetically balanced (RKB) 42,43 basis sets is the DFT analogy of the modified Dirac equation 44,45 and has been described previously.…”
Section: ■ Computational Detailsmentioning
confidence: 99%
“…For [WO­(bdt) 2 ] − , a DMF/CH 3 CN “mixture” with ε = 36.4 is used. A variety of possible solvents (CH 2 Cl 2 , DMF, and THF) were mentioned for the EPR measurements of [Tp*WO­(XPh) 2 ] (X = O, S), without further specifying the one actually used …”
Section: Computational Detailsmentioning
confidence: 99%